Fibrillated chemically modified cellulose fibers

Fibrillated chemically modified cellulose fibers with controlled diameter and crystallinity address the challenges of using cellulose nanofibers, offering enhanced water retention and thixotropy for improved paper strength and cost-effectiveness.

JP7605945B2Active Publication Date: 2024-12-24NIPPON PAPER IND CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023194271
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-04
Filing Date
2023-11-15
Publication Date
2024-12-24
Estimated Expiration
2040-03-05

AI Technical Summary

Technical Problem

Cellulose nanofibers, with their high thixotropy and water retention properties, are difficult to use due to their fine size, leading to issues like slipping through wires and poor paper strength, and are expensive to manufacture.

Method used

Developing fibrillated chemically modified cellulose fibers with a fiber diameter greater than 500 nm, high crystallinity, and controlled anionization, achieved through chemical modification and fibrillation using paper manufacturing equipment like a refiner, to enhance water retention and thixotropy.

Benefits of technology

The modified fibers exhibit improved water retention and thixotropy, providing higher paper strength and yield with lower costs, suitable for various applications including food, pharmaceuticals, cosmetics, and paper manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605945000001
    Figure 0007605945000001
  • Figure 0007605945000002
    Figure 0007605945000002
Patent Text Reader

Abstract

To provide a fibrillated, chemically modified cellulose fiber used as a papermaking additive and having a lower fibrillation degree than cellulose nanofiber.SOLUTION: A fibrillated, chemically modified cellulose fiber used as a papermaking additive has a cellulose I-type crystallinity of 50% or over, an anion conversion degree of 0.10 meq / g or over and 2.00 meq / g or under, an average fiber diameter of 10 μm or over, an aspect ratio of 10-100, and a water retention property of 15 or over.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to fibrillated chemically modified cellulose fibers. [Background technology]

[0002] In the papermaking process, a composition in which pulp or pigment is dispersed in water is used. The water retention of the composition is important from the viewpoint of improving the efficiency of the manufacturing process and the quality of the product. For example, in the case of pulp slurry, which is the raw material of base paper, the water retention of the pulp slurry has a significant effect on the drainage of water on the wire and the dispersibility of the pulp, and as a result, it has a significant effect on the paper strength, air resistance, and bulk of the manufactured paper. In addition, the water retention of the pigment coating liquid changes the degree of penetration of the adhesive into the base paper, which has a significant effect on the strength and adhesiveness of the pigment coating layer and the base paper. In recent years, cellulose nanofibers made from cellulose have been actively studied, and for example, Patent Document 1 discloses a composition containing cellulose nanofibers with a number average fiber diameter of 2 nm to 500 nm. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-110085 A Summary of the Invention [Problem to be solved by the invention]

[0004] Cellulose nanofibers are cellulose fibers that have been defibrated to the nano order with an average fiber diameter of less than 500 nm. In particular, cellulose nanofibers with a fiber diameter of around 4 nm correspond to single microfibrils, which are the basic units of cellulose bundles in plant cell walls. Such cellulose nanofibers have high thixotropy and water retention and can be used in a variety of fields, but because they are very fine, they may be difficult to use depending on the application. For example, when using cellulose nanofibers as a papermaking additive, if the amount is small, problems such as poor yield due to the tendency for them to slip through the wire and difficulty in achieving paper strength may occur. In addition, cellulose nanofibers are expensive to produce.

[0005] The present inventors considered that if the water retention and thixotropy of a composition could be improved by using cellulose fibers that are less defibrated than cellulose nanofibers, advantages such as the possibility of producing paper with increased strength at low cost could be obtained. An object of the present invention is to provide fibrillated chemically modified cellulose fibers that are less defibrated than cellulose nanofibers. [Means for solving the problem]

[0006] As a result of extensive research, the inventors have found that by treating chemically modified pulp with papermaking equipment, such as a refiner, it is possible to provide fibrillated chemically modified cellulose fibers having a fiber diameter of greater than 500 nm and which are less defibrated than cellulose nanofibers.

[0007] The present invention includes, but is not limited to, the following: [1] A fibrillated chemically modified cellulose fiber having a crystallinity of 50% or more for cellulose type I, a degree of anionization of 0.10 meq / g or more and 2.00 meq / g or less, and an average fiber diameter of more than 500 nm. [2] 40 mL of a slurry having a solid content of 0.3% by mass was prepared using water, and the slurry was then centrifuged at 25,000 G for 30 minutes at 30° C. to separate the aqueous phase and the sediment, and the following formula was calculated: Water retention capacity=(B+C-0.003×A) / (0.003×AC) (where A is the mass of the slurry to be centrifuged, B is the mass of the separated sediment, and C is the mass of the solids in the separated aqueous phase) The fibrillated chemically modified cellulose fiber according to [1], having a water retention capacity of 15 or more as calculated using the following formula: [3] The fibrillated chemically modified cellulose fiber according to [1] or [2], which has a Brookfield viscosity (25°C, 60 rpm) of 2500 mPa s or less when dispersed in water at 1% solids by mass. [4] A fibrillated chemically modified cellulose fiber in which, in an aqueous dispersion having a solid content of 1% by mass, the viscosity A measured at a shear rate of 0.01 / sec divided by the viscosity B measured at a shear rate of 1000 / sec (A / B) is 100 or more. [5] The fibrillated chemically modified cellulose fiber according to [4], in an aqueous dispersion having a solid content of 1% by mass, the viscosity A measured at a shear rate of 0.01 / sec is 1,000 to 10,000,000 mPa s, and the viscosity B measured at a shear rate of 1,000 / sec is 1 to 1,000 mPa s. [6] The fibrillated chemically modified cellulose fiber according to [4] or [5], which has a viscosity (25°C, 60 rpm) of 40 to 4,000 mPa s when dispersed in water at 1% solids by mass. [7] The fibrillated chemically modified cellulose fiber according to any one of [4] to [6], having an aspect ratio of 10 to 100. [8] The chemically modified cellulose fiber according to any one of [4] to [7], having a crystallinity of cellulose type I of 50% or more, a degree of anionization of 0.08 meq / g or more and 2.50 meq / g or less, and an average fiber diameter of more than 500 nm. [9] The fibrillated chemically modified cellulose fiber according to any one of [1] to [8], wherein the chemically modified cellulose in the fibrillated chemically modified cellulose fiber is a carboxylated cellulose obtained by oxidizing a cellulose raw material using an N-oxyl compound, a compound selected from the group consisting of bromides, iodides and mixtures thereof, and an oxidizing agent.

[10] The fibrillated chemically modified cellulose fiber according to [9], wherein the chemically modified cellulose in the fibrillated chemically modified cellulose fiber is a carboxylated cellulose having a carboxyl group amount of 0.1 to 2.5 mmol / g relative to the bone dry mass of the fibrillated chemically modified cellulose fiber.

[11] The fibrillated, chemically modified cellulose fiber according to any one of [1] to [8], wherein the chemically modified cellulose in the fibrillated, chemically modified cellulose fiber is carboxymethyl cellulose.

[12] The fibrillated chemically modified cellulose fiber according to

[11] , wherein the chemically modified cellulose in the fibrillated chemically modified cellulose fiber is a carboxymethylated cellulose having a carboxymethyl substitution degree per glucose unit of the chemically modified cellulose of 0.01 to 0.50. Effect of the Invention

[0008] The fibrillated chemically modified cellulose fiber of the present invention has high water retention and high thixotropy (the value (A / B) obtained by dividing the viscosity A measured at a shear rate of 0.01 / sec by the viscosity B measured at a shear rate of 1000 / sec is 100 or more). In addition, since the fiber has remaining crystallinity despite being chemically modified, it is considered that the fiber has a shape retention and strength imparting effect in addition to the water retention imparting effect due to chemical modification. In particular, when the fiber has high thixotropy, it has a shape retention improving effect when added to gel-like substances (foods, medicines, etc.) in viscosity adjusting applications such as thickeners. In addition, since the fiber is fibrillated to a degree that maintains a fiber diameter of more than 500 nm, the fiber diameter is not too fine (moderate fibrillation), and it exhibits high water retention and moderate thickening compared to, for example, chemically modified cellulose that is not defibrated or fibrillated, and it is considered that the fiber has an effect of imparting higher strength to paper with a small amount as a papermaking additive compared to finely defibrated chemically modified cellulose nanofibers. The fibrillated chemically modified cellulose fibers of the present invention are expected to provide new effects and applications that are difficult to achieve with conventional non-fibrillated chemically modified cellulose, finely defibrated cellulose nanofibers, or non-chemically modified fibrillated cellulose. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] <Chemically modified cellulose> The chemically modified cellulose used in the fibrillated chemically modified cellulose fiber of the present invention is one in which the cellulose chains constituting the fiber have been chemically modified. The types of chemically modified cellulose are not limited to these, but examples include carboxylated cellulose in which a carboxyl group has been introduced, carboxyalkylated cellulose in which a carboxyalkyl group such as a carboxymethyl group has been ether-bonded, and phosphoric acid esterified cellulose in which a phosphoric acid group has been introduced. Preferred types of chemical modification include oxidation (carboxylation), etherification (e.g., carboxyalkylation), cationization, and esterification, and among these, oxidation (carboxylation) and carboxyalkylation are more preferred. The production methods of these will be described later.

[0010] Chemically modified cellulose may take the form of a salt, and the term "chemically modified cellulose" as used herein includes salt-type chemically modified cellulose. Examples of salt-type chemically modified cellulose include those that form metal salts such as sodium salts.

[0011] The chemically modified cellulose used in the fibrillated chemically modified cellulose fiber of the present invention maintains at least a part of its fibrous shape even when dispersed in water. That is, when an aqueous dispersion of the chemically modified cellulose fiber is observed with an electron microscope or the like, a fibrous substance can be observed, and when measured by X-ray diffraction, a peak of cellulose type I crystals can be observed.

[0012] <Fibrillated chemically modified cellulose fibers> The fibrillated chemically modified cellulose fibers of the present invention are obtained by moderately beating or defibrating (fibrillating) a chemically modified cellulose raw material using a refiner or the like. Compared to chemically modified cellulose fibers that have not been beaten or defibrated, fibrillated chemically modified cellulose fibers have cellulose microfibril fluff on the fiber surface. In addition, compared to chemically modified cellulose nanofibers, the fiber diameter is larger and the fiber surface is efficiently fuzzed (external fibrillation) while minimizing the fiber itself (internal fibrillation).

[0013] Furthermore, the fibrillated chemically modified cellulose fibers of the present invention have characteristics such as high water retention and high thixotropy due to the chemical modification, compared to fibrillated cellulose fibers that are not chemically modified.

[0014] In addition, the fibrillated chemically modified cellulose fibers obtained by fibrillating the chemically modified cellulose raw material of the present invention have the characteristic that, compared to cellulose raw material that is not chemically modified and then chemically modified, the cellulose fibers are chemically modified during fibrillation, and therefore the strong hydrogen bonds present between the fibers are weakened, making it easier for the fibers to come apart during fibrillation and resulting in less damage to the fibers.

[0015] The fibrillated chemically modified cellulose fibers of the present invention have an average fiber diameter of 500 nm or more, preferably 1 μm or more, and more preferably 10 μm or more. The upper limit of the average fiber diameter is preferably 60 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and even more preferably 20 μm or less. By performing moderate fibrillation to an extent that the average fiber diameter falls within this range, the fibers exhibit higher water retention and higher thixotropy than undefibrated cellulose fibers, and can achieve higher strength imparting effects and yield improvement effects even in small amounts compared to finely defibrated cellulose nanofibers.

[0016] The average fiber length is preferably 200 μm or more, more preferably 250 μm or more, more preferably 300 μm or more, and more preferably 500 μm or more. The upper limit of the average fiber length is not particularly limited, but is preferably 3000 μm or less, more preferably 2500 μm or less, more preferably 2000 μm or less, more preferably 1500 μm or less, more preferably 1100 μm or less, and more preferably 900 μm or less. According to the present invention, since a chemically modified cellulose raw material is used for beating or defibration, fibrillation can be promoted without extremely shortening the fibers. In addition, since the affinity with water is improved by the chemical modification, water retention can be increased even when the fiber length is long.

[0017] The average fiber diameter and the average fiber length can be determined by an image analysis type fiber analyzer such as the L&W Fiber Tester Plus manufactured by ABB Corporation or the Fractionator manufactured by Valmet Co., Ltd. Specifically, they can be measured by the following method: An aqueous dispersion of chemically modified cellulose fiber diluted to a solid content concentration of 0.25% by mass was subjected to a fractionator, and the length-weighted fiber width and length-weighted average fiber length were determined (n=2).

[0018] The aspect ratio of the fibrillated chemically modified cellulose fibers is preferably 10 or more, more preferably 15 or more, more preferably 20 or more, and even more preferably 30 or more. There is no particular upper limit to the aspect ratio, but it is preferably 1000 or less, more preferably 100 or less, and even more preferably 80 or less. The aspect ratio can be calculated by the following formula: Aspect ratio = average fiber length / average fiber diameter.

[0019] The fibrillation rate (Fibrillation %) of the fibrillated chemically modified cellulose fiber measured using a fractionator manufactured by Valmet Co., Ltd. is preferably 1.0% or more, more preferably 1.2% or more, more preferably 1.5% or more, more preferably 2.5% or more, and even more preferably 3.5% or more. The fibrillation rate varies depending on the type of cellulose raw material used, but it is considered that fibrillation has been performed within the above range. In addition, in the present invention, it is preferable to perform fibrillation so that the fibrillation rate (f0) of the chemically modified cellulose raw material before fibrillation is improved. If the fibrillation rate of the fibrillated chemically modified cellulose fiber is f, the difference in the fibrillation rates Δf=f-f0 may be more than 0, and is preferably 0.1% or more, more preferably 0.2% or more, more preferably 0.3% or more, more preferably 1.0% or more, and even more preferably 2.5% or more.

[0020] <Crystallization degree of cellulose type I> The degree of crystallinity of cellulose in the fibrillated chemically modified cellulose fiber of the present invention is 50% or more, and more preferably 60% or more, for crystalline type I. The crystallinity of cellulose can be controlled by the degree of chemical modification. There is no particular upper limit to the degree of crystallinity of cellulose type I. In reality, the upper limit is thought to be about 90%.

[0021] The method for measuring the crystallinity of cellulose type I of chemically modified cellulose fibers is as follows: The sample is placed in a glass cell and measured using an X-ray diffraction measuring device (LabX XRD-6000, manufactured by Shimadzu Corporation). The degree of crystallinity is calculated using the method of Segal et al., and is calculated from the diffraction intensity of the 002 plane at 2θ = 22.6° and the diffraction intensity of the amorphous part at 2θ = 18.5° using the diffraction intensity of the X-ray diffraction pattern at 2θ = 10° to 30° as the baseline, according to the following formula. Xc = (I002c - Ia) / I002c x 100 Xc = Crystallinity of cellulose type I (%) I002c: 2θ=22.6°, diffraction intensity of 002 plane Ia: 2θ=18.5°, diffraction intensity of the amorphous part.

[0022] <Degree of anionization> The degree of anionization (also referred to as anion charge density) of the fibrillated chemically modified cellulose fiber of the present invention is usually 2.50 meq / g or less, preferably 2.30 meq / g or less, more preferably 2.00 meq / g or less, more preferably 1.50 meq / g or less, more preferably 1.30 meq / g or less, more preferably 1.00 meq / g or less, and even more preferably 0.80 meq / g or less. It is considered that the chemically modified cellulose fiber having such an anionization degree is not locally modified but is uniformly modified throughout the cellulose as compared with the chemically modified cellulose fiber having a higher degree of anionization, and it is considered that the effects specific to the chemically modified cellulose fiber, such as water retention, can be obtained more stably. The lower limit is usually 0.08 meq / g or more, preferably 0.10 meq / g or more, and more preferably 0.30 meq / g or more, but is not particularly limited. The degree of anionization can be calculated from the equivalent amount of diallyldimethylammonium chloride (DADMAC) required to neutralize the anionic groups in a unit mass of chemically modified cellulose fiber. In the present invention, the method for measuring the degree of anionization is as follows: Chemically modified cellulose fibers are dispersed in water to prepare an aqueous dispersion with a solid content of 10 g / L, and stirred at 1000 rpm for 10 minutes or more using a magnetic stirrer. The resulting slurry is diluted to 0.1 g / L, and 10 ml of the solution is taken and titrated with 1 / 1000 normality diallyldimethylammonium chloride (DADMAC) using a streaming current detector (Mutek Particle Charge Detector 03). The amount of DADMAC added until the streaming current becomes zero is used to calculate the degree of anionization according to the following formula: q=(V×c) / m q: degree of anionization (meq / g) V: Amount of DADMAC added until the streaming current becomes zero (L) c: DADMAC concentration (meq / L) m: mass (g) of chemically modified cellulose fiber in the measurement sample.

[0023] <Water retention capacity> The water retention capacity of the fibrillated chemically modified cellulose fibers of the present invention is preferably 15 or more as measured by the following method. The method for measuring the water retention capacity is as follows: Prepare 40 mL of a 0.3 mass% slurry of fibrillated chemically modified cellulose fibers (medium: water). Let the mass of this slurry at this time be A. Next, centrifuge the entire amount of the slurry at 30 °C and 25,000 G for 30 minutes using a high-speed cooling centrifuge to separate the aqueous phase and the sediment. Let the mass of the sediment at this time be B. Also, put the aqueous phase in an aluminum cup and dry it at 105 °C for one day and night to remove water, and measure the mass of the solid content in the aqueous phase. Let the mass of the solid content in this aqueous phase be C. Use the following formula to calculate the water retention capacity: Water retention capacity = (B + C - 0.003×A) / (0.003×A - C).

[0024] As shown in the above formula, the water retention capacity corresponds to the mass of water in the sediment relative to the mass of the solid content of the fibers in the sediment. The larger the value, the higher the ability of the fibers to retain water. The water retention capacity of the fibrillated chemically modified cellulose fibers of the present invention is preferably 15 or more, more preferably 20 or more, and even more preferably 30 or more. The upper limit is not particularly limited, but is realistically considered to be about 200 or less.

[0025] Note that the above method for measuring the water retention capacity is for fibrillated fibers, and is not usually applicable to non-fibrillated or defibrated fibers or cellulose nanofibers defibrated to single microfibrils. If an attempt is made to measure the water retention capacity of non-fibrillated or defibrated cellulose fibers by the above method, a dense sediment cannot be formed under the above centrifugation conditions, and it is difficult to separate the sediment and the aqueous phase. Also, cellulose nanofibers hardly sediment under the above centrifugation conditions.

[0026] <B-type viscosity> The fibrillated chemically modified cellulose fiber of the present invention, when dispersed in water as a dispersion medium (aqueous dispersion), preferably has a B-type viscosity (25°C, 60 rpm) of 4000 mPa·s or less, more preferably 3000 mPa·s or less, more preferably 2000 mPa·s or less, more preferably 1500 mPa·s or less, more preferably 1000 mPa·s or less, more preferably 600 mPa·s or less, and more preferably 300 mPa·s or less. When the B-type viscosity of the chemically modified cellulose fiber is as low as this, the material has good handleability despite being fibrillated. The lower limit of the B-type viscosity is not particularly limited, but is preferably 10 mPa·s or more, more preferably 20 mPa·s or more, even more preferably 40 mPa·s or more, even more preferably 50 mPa·s or more, and even more preferably 60 mPa·s or more. In the present invention, the B-type viscosity is measured as follows: The fibrillated chemical cellulose fibers that have been left to stand for at least one day after fibrillation are weighed into a polypropylene container and dispersed in 160 ml of ion-exchanged water to prepare an aqueous dispersion with a solid content of 1% by mass. The aqueous dispersion is left to stand for 3 hours in a water bath adjusted to 25°C. The viscosity is then measured after 1 minute at a rotation speed of 60 rpm using a B-type viscometer (manufactured by Toki Sangyo Co., Ltd.) in accordance with the method of JIS-Z-8803.

[0027] <Thixotropy> In the fibrillated chemically modified cellulose fiber of the present invention, in an aqueous dispersion having a solid content of 1% by mass, the viscosity A measured at a shear rate of 0.01 / sec divided by the viscosity B measured at a shear rate of 1000 / sec (A / B) is preferably 100 or more. A / B is more preferably 500 or more, and even more preferably 1000 or more. A higher A / B indicates higher thixotropy. There is no particular upper limit for A / B, but in practice it is about 20,000.

[0028] Thixotropy refers to the property that the viscosity gradually decreases when subjected to shear stress and gradually increases when stationary. Viscosity A is preferably 1000 mPa·s or more, more preferably 1500 mPa·s or more, and even more preferably 2000 mPa·s or more. The upper limit of viscosity A is preferably 10,000,000 mPa or less, more preferably 5,000,000 mPa·s or less, and even more preferably 3,000,000 mPa·s or less. Viscosity B is preferably 1000 mPa·s or less, more preferably 500 mPa·s or less, more preferably 300 mPa·s or less, and even more preferably 100 mPa·s or less. The lower limit of viscosity B is preferably 1 mPa·s or more, and even more preferably 10 mPa·s or more. In the present invention, the method for measuring viscosities A and B is as follows: Water is added to the chemically modified cellulose fiber to prepare an aqueous dispersion with a solid content of 1.0% by mass. The obtained aqueous dispersion is adjusted to 25°C, and the viscosity A is measured at a shear rate of 0.01 / sec and the viscosity B is measured at a shear rate of 1000 / sec using a viscoelastic rheometer MCR301 (manufactured by Anton Paar). A parallel plate (PP25) is used for the measurement, and the gap between the measurement sections is set to 1 mm.

[0029] <Other> The fibrillated chemically modified cellulose fiber of the present invention, when dispersed in water with a solid content concentration of 1.0% by mass, preferably has an electrical conductivity of 500 mS / m or less. More preferably, it is 300 mS / m or less, even more preferably, it is 200 mS / m or less, even more preferably, it is 100 mS / m or less, and even more preferably, it is 70 mS / m or less. The lower limit of the electrical conductivity is preferably 5 mS / m or more, and more preferably, it is 10 mS / m or more. The electrical conductivity can be measured by the following method: 200 g of an aqueous dispersion of fibrillated chemically modified cellulose fibers with a solid content of 1.0% by mass was prepared and thoroughly stirred, after which the electrical conductivity was measured using an electrical conductivity meter (HORIBA ES-71).

[0030] The fibrillated chemically modified cellulose fibers of the present invention preferably have a BET specific surface area of ​​30 m 2 / g or more, more preferably 50m 2 / g or more, more preferably 70m 2 / g or more, more preferably 100m 2 / g or more. If the BET specific surface area is high, for example, when used as a papermaking additive, it is easier to bind to pulp, which has the advantage of improving yield and increasing the effect of adding strength to paper. The BET specific surface area can be measured by the following method, referring to the nitrogen gas adsorption method (JIS Z 8830): (1) Approximately 2% slurry of fibrillated chemically modified cellulose fibers (dispersion medium: water) is separated and placed in a centrifuge container so that the solid content is approximately 0.1 g, and 100 ml of ethanol is added. (2) Add a stirrer and stir at 500 rpm for at least 30 minutes. (3) Remove the stirrer and sediment the fibrillated chemically modified cellulose fibers in a centrifuge at 7,000 G for 30 minutes at 30°C. (4) The supernatant is removed while trying to avoid removing as much of the fibrillated chemically modified cellulose fibers as possible. (5) Add 100 ml of ethanol, add a stir bar, stir under conditions (2), centrifuge under conditions (3), and remove the supernatant under conditions (4). Repeat this process three times. (6) The solvent in (5) is changed from ethanol to t-butanol, and the stirring, centrifugation, and removal of the supernatant are repeated three times in the same manner as in (5) at room temperature above the melting point of t-butanol. (7) After the final solvent removal, add 30 ml of t-butanol, mix gently, then transfer to a recovery flask and freeze in an ice bath. (8) Chill in the freezer for at least 30 minutes. (9) Place in a freeze-dryer and freeze-dry for 3 days. (10) Perform BET measurement (pretreatment conditions: 2 hours at 105°C under nitrogen flow, relative pressure 0.01 to 0.30, sample amount approximately 30 mg).

[0031] The Shopper-Riegler freeness of the fibrillated chemically modified cellulose fiber of the present invention is not particularly limited, but is preferably 1°SR or more, more preferably 10°SR or more, and more preferably 25°SR or more. The method for measuring the Shopper-Riegler freeness is in accordance with JIS P 82121-1:2012, and specifically, is as follows: The fibrillated chemically modified cellulose fibers are dispersed in water to prepare an aqueous dispersion with a solid content of 10 g / L, which is then stirred at 1000 rpm for 10 minutes or more using a magnetic stirrer. The resulting slurry is diluted to 2 g / L. A 60 mesh screen (wire diameter 0.17 mm) is set on a Mutec DFR-04, and the amount of liquid passing through the mesh from a 1000 ml test solution is measured for 60 seconds, and the Shopper-Riegler freeness is calculated according to the method of JIS P 8121-1:2012.

[0032] The Shopper-Riegler freeness is a measure of the degree of drainage of a fiber suspension, with the lower limit being 0°SR and the upper limit being 100°SR, and the closer the Shopper-Riegler freeness is to 100°SR, the less drainage (amount of drainage) is indicated. The Shopper-Riegler freeness of the fibrillated chemically modified cellulose fiber of the present invention is not particularly limited, but the lower limit is preferably 1°SR or more, more preferably 10°SR or more, more preferably 25°SR or more, more preferably 40°SR or more, and even more preferably 50°SR or more. The upper limit is not particularly limited, and is 100°SR or less.

[0033] The fibrillated chemically modified cellulose fiber of the present invention, when dispersed in water with a solid content of 1% by mass, preferably has a transparency (transmittance of 660 nm light) of less than 60%, more preferably 40% or less, even more preferably 30% or less, even more preferably 20% or less, and even more preferably 10% or less. There is no particular lower limit and it may be 0% or more. When the transparency is in this range, the degree of fibrillation is appropriate and the effects of the present invention are easily obtained. The transparency can be measured by the following method: An aqueous dispersion of fibrillated chemically modified cellulose fibers (solid content 1% (w / v), dispersion medium: water) is prepared, and the transmittance of light with a wavelength of 660 nm is measured using a UV-VIS spectrophotometer UV-1800 (Shimadzu Corporation) with a square cell with an optical path length of 10 mm.

[0034] The fibrillated chemically modified cellulose fibers of the present invention become translucent to white gel, creamy or paste-like when the solid content concentration is about 2% or more in water as a dispersion medium.

[0035] The fibrillated chemically modified cellulose fibers may be in the form of a dispersion obtained after production, but may be dried or redispersed in water as necessary. The drying method is not particularly limited, and known methods such as freeze drying, spray drying, tray drying, drum drying, belt drying, thin spreading on a glass plate or the like and drying, fluidized bed drying, microwave drying, and heated fan reduced pressure drying can be used. After drying, the fibers may be pulverized using a cutter mill, hammer mill, pin mill, jet mill, or the like as necessary. The method of redispersing in water is also not particularly limited, and known dispersing devices can be used.

[0036] The applications of the fibrillated chemically modified cellulose fibers are not particularly limited, but since the fibrillated chemically modified cellulose fibers of the present invention have excellent thixotropy and water retention, they are considered to be particularly suitable for applications requiring shape retention and water retention. In addition, since the degree of defibration is not too strong and the fiber diameter is appropriate, they are considered to be particularly suitable for applications requiring fiber strength or applications requiring high fiber yield. However, they may be used for other applications. The fields in which fibrillated chemically modified cellulose fibers are used are not limited, and they can be used in a variety of fields in which additives are generally used, such as food, feed, cosmetics, pharmaceuticals, papermaking, various chemical products, paints, sprays, pesticides, civil engineering, construction, electronic materials, flame retardants, household goods, adhesives, cleaning agents, fragrances, and lubricating compositions, as thickeners, gelling agents, starches, food additives, excipients, paint additives, adhesive additives, papermaking additives, abrasives, rubber and plastic compounding materials, water retention agents, shape retention agents, muddy water regulators, filter aids, and overflow prevention agents.

[0037] Examples of food products include, but are not limited to, water retention agents, shape retention agents, viscosity regulators, emulsion stabilizers, dispersion stabilizers, etc. Examples of foods that can be used include, but are not limited to, beverages (cocoa, juices containing fiber and fruit pulp, shiruko, amazake, lactic acid bacteria drinks, fruit milk, etc.), soups (corn soup, ramen soup, miso soup, consommé, etc.), sauces, dressings, ketchup, mayonnaise, jams, yogurt, whipped cream, dried foods (dried processed foods, instant ramen, pasta noodles, etc.), gluten-free pasta, ice cream, monaka, sherbet, polyjuice, confectioneries (gummy candies, soft candies, jellies, cookies, etc.), meringues, bread, gluten-free bread, fillings, pancakes, pastes, edible films, etc.

[0038] When added to food, the amount added can be appropriately selected depending on the expected effect, but for example, it is preferably 0.1 to 20 mass % relative to the total mass of the food, more preferably 0.5 to 15 mass %, and even more preferably 0.5 to 10 mass %.

[0039] For pharmaceutical purposes, the composition can be used, for example and without limitation, as a water retention imparting agent, shape retention imparting agent, viscosity modifier, emulsion stabilizer, dispersion stabilizer, etc. For pharmaceutical purposes, the composition can be used, for example and without limitation, as a tablet, ointment, bandage, cataplasm, hand cream, toothpaste, etc.

[0040] When added to a pharmaceutical product, the amount added can be appropriately selected depending on the expected effect, but for example, the amount is preferably 0.1 to 30 mass%, more preferably 0.5 to 20 mass%, and even more preferably 0.5 to 10 mass%, relative to the total mass of the pharmaceutical product.

[0041] For cosmetics, for example, but not limited to, it can be used as a water retention imparting agent, shape retention imparting agent, viscosity adjusting agent, emulsion stabilizer, dispersion stabilizer, etc. For cosmetics that can be used, for example, but not limited to, face powder, foundation, scrub face wash, pack, face wash foam, face wash cream, hair mousse, shampoo, soap, lotion, hair color, hair bleach, mascara, eyeliner, nail, antiperspirant, etc.

[0042] The amount added to a cosmetic product can be appropriately selected depending on the expected effect, but is preferably 0.1 to 30 mass %, more preferably 0.5 to 20 mass %, and even more preferably 0.5 to 10 mass %, relative to the total mass of the cosmetic product.

[0043] For feed, for example, but not limited to, it can be used as a water retention imparting agent, a shape retention imparting agent, a viscosity adjusting agent, an emulsion stabilizer, a dispersion stabilizer, etc. For feed, for example, but not limited to, moist pellets, expansion pellets, milk substitutes for cows, etc. can be used.

[0044] The amount added to feed can be appropriately selected depending on the expected effect, but is preferably 0.1 to 20 mass%, more preferably 0.5 to 15 mass%, and even more preferably 0.5 to 10 mass%, based on the total mass of the feed.

[0045] Examples of papermaking agents include, but are not limited to, water retention agents, shape retention agents, viscosity regulators, emulsion stabilizers, and dispersion stabilizers. They can also be used as papermaking chemicals, such as surface sizing agents, retention improvers, paper strength agents, coating agents, and bulky paper additives.

[0046] When used as a papermaking chemical, the amount added can be appropriately selected depending on the expected effect, but for example, it is preferably 0.1 to 30 mass % relative to the total mass of the papermaking chemical, more preferably 0.5 to 20 mass %, and even more preferably 0.5 to 10 mass %.

[0047] Examples of paints that can be used include, but are not limited to, water retention agents, shape retention agents, viscosity adjusters, emulsion stabilizers, dispersion stabilizers, etc. Examples of paints that can be used include, but are not limited to, matte paints, architectural paints, and automotive paints.

[0048] The amount added to the paint can be appropriately selected depending on the expected effect, but is preferably 0.1 to 30 mass %, more preferably 0.5 to 20 mass %, and even more preferably 0.5 to 10 mass %, based on the total mass of the paint.

[0049] <Method for producing fibrillated chemically modified cellulose fibers> The fibrillated chemically modified cellulose fiber of the present invention can be produced by first preparing a chemically modified cellulose raw material and then fibrillating it. As the types of chemical modification, as described above, for example, carboxylation, carboxyalkylation, phosphorylation, etc. of cellulose can be mentioned, but are not limited to these. The chemically modified cellulose raw material to be subjected to fibrillation may be a commercially available product, or may be produced by chemically modifying the cellulose raw material described below by the method described below.

[0050] <Cellulose raw material> The cellulose that is the raw material for the fibrillated chemically modified cellulose fiber of the present invention is not particularly limited, and examples thereof include those derived from plants, animals (e.g., ascidians), algae, microorganisms (e.g., acetic acid bacteria (Acetobacter)), and microbial products. Examples of those derived from plants include wood, bamboo, hemp, jute, kenaf, agricultural waste, cloth, and pulp (softwood unbleached kraft pulp (NUKP), softwood bleached kraft pulp (NBKP), hardwood unbleached kraft pulp (LUKP), hardwood bleached kraft pulp (LBKP), softwood unbleached sulfite pulp (NUSP), softwood bleached sulfite pulp (NBSP), thermomechanical pulp (TMP), softwood dissolving pulp, hardwood dissolving pulp, recycled pulp, waste paper, etc.). Cellulose powder obtained by pulverizing the above-mentioned cellulose raw material may also be used. As the cellulose raw material, any one or a combination of these may be used, but cellulose fibers derived from plants or microorganisms are preferred, cellulose fibers derived from plants are more preferred, and wood-based pulp is even more preferred.

[0051] In order to maintain a crystallinity of cellulose type I of 50% or more in the fibrillated chemically modified cellulose fiber, it is preferable to use cellulose having a high crystallinity of cellulose type I as the raw material. The crystallinity of the cellulose raw material is preferably 70% or more, more preferably 80% or more. The method for measuring the crystallinity of cellulose type I is the same as that described above.

[0052] <Carboxylation of cellulose raw materials> As an example of a chemically modified cellulose raw material, a carboxylated (introduction of a carboxyl group into cellulose, also called "oxidation") cellulose raw material can be used. The carboxylated cellulose raw material (also called "oxidized cellulose raw material") may be a commercially available product, or may be produced by carboxylating (oxidizing) the above-mentioned cellulose raw material by a known method. The amount of carboxyl groups is preferably 0.1 to 2.5 mmol / g, more preferably 0.6 mmol / g to 2.5 mmol / g, and even more preferably 1.0 mmol / g to 2.0 mmol / g, based on the bone dry mass of the carboxylated cellulose fiber.

[0053] The amount of carboxyl groups in carboxylated cellulose can be measured by the following method: 60 ml of a 0.5% by mass slurry (aqueous dispersion) of carboxylated cellulose is prepared, and a 0.1 M aqueous hydrochloric acid solution is added to adjust the pH to 2.5. A 0.05 N aqueous sodium hydroxide solution is then added dropwise to measure the electrical conductivity until the pH reaches 11. The electrical conductivity is calculated from the amount of sodium hydroxide (a) consumed in the neutralization stage of the weak acid, where the change in electrical conductivity is gradual, using the following formula: Amount of carboxyl groups [mmol / g carboxylated cellulose] = a [ml] × 0.05 / mass of carboxylated cellulose [g].

[0054] The amount of carboxyl groups in the carboxylated cellulose raw material before fibrillation is usually the same as the amount of carboxyl groups in the carboxylated cellulose fibers after fibrillation.

[0055] One example of a carboxylation (oxidation) method is a method in which a cellulose raw material is oxidized in water using an oxidizing agent in the presence of an N-oxyl compound and a compound selected from the group consisting of bromides, iodides, and mixtures thereof. This oxidation reaction selectively oxidizes the primary hydroxyl group at the C6 position of the glucopyranose ring on the cellulose surface, resulting in the formation of aldehyde groups and carboxyl groups (-COOH) or carboxylate groups (-COO - The concentration of the cellulose raw material during the reaction is not particularly limited, but is preferably 5% by mass or less.

[0056] The N-oxyl compound refers to a compound capable of generating nitroxy radicals. Any compound that can promote the target oxidation reaction can be used as the N-oxyl compound. For example, 2,2,6,6-tetramethylpiperidine-1-oxy radical (TEMPO) and its derivatives (e.g., 4-hydroxyTEMPO) can be mentioned. The amount of the N-oxyl compound used is not particularly limited as long as it is a catalytic amount capable of oxidizing the cellulose raw material. For example, 0.01 mmol to 10 mmol is preferable, 0.01 mmol to 1 mmol is more preferable, and 0.05 mmol to 0.5 mmol is even more preferable for 1 g of bone-dry cellulose raw material. In addition, about 0.1 mmol / L to 4 mmol / L is preferable for the reaction system.

[0057] Bromides are compounds containing bromine, examples of which include alkali metal bromides that can dissociate and ionize in water. Also, iodides are compounds containing iodine, examples of which include alkali metal iodides. The amount of bromide or iodide used can be selected within a range that can promote the oxidation reaction. The total amount of bromide and iodide is, for example, preferably 0.1 mmol to 100 mmol, more preferably 0.1 mmol to 10 mmol, and even more preferably 0.5 mmol to 5 mmol, per 1 g of bone-dry cellulose raw material.

[0058] The oxidizing agent may be a known one, such as halogen, hypohalous acid, halous acid, perhalogen acid or their salts, halogen oxide, or peroxide. Among them, sodium hypochlorite is preferable because it is inexpensive and has a low environmental impact. The appropriate amount of the oxidizing agent to be used is, for example, preferably 0.5 mmol to 500 mmol, more preferably 0.5 mmol to 50 mmol, even more preferably 1 mmol to 25 mmol, and most preferably 3 mmol to 10 mmol, per 1 g of bone-dry cellulose raw material. Also, for example, 1 mol to 40 mol is preferable per 1 mol of the N-oxyl compound.

[0059] The oxidation process of the cellulose raw material can proceed efficiently even under relatively mild conditions. Therefore, the reaction temperature is preferably 4°C to 40°C, or may be room temperature of about 15°C to 30°C. As the reaction proceeds, carboxyl groups are generated in the cellulose chain, and a decrease in the pH of the reaction solution is observed. In order to efficiently proceed with the oxidation reaction, it is preferable to add an alkaline solution such as an aqueous sodium hydroxide solution to maintain the pH of the reaction solution at about 8 to 12, preferably about 10 to 11. The reaction medium is preferably water, because it is easy to handle and does not easily cause side reactions. The reaction time in the oxidation reaction can be appropriately set according to the degree of progress of the oxidation, and is usually 0.5 hours to 6 hours, for example, about 0.5 hours to 4 hours.

[0060] The oxidation reaction may also be carried out in two stages. For example, the oxidized cellulose obtained by filtration after completion of the first-stage reaction can be oxidized again under the same or different reaction conditions, allowing efficient oxidation without reaction inhibition by table salt produced as a by-product in the first-stage reaction.

[0061] Another example of the carboxylation (oxidation) method is a method in which the cellulose raw material is oxidized by contacting it with an ozone-containing gas. This oxidation reaction oxidizes at least the 2- and 6-hydroxyl groups of the glucopyranose ring and decomposes the cellulose chain. The ozone concentration in the ozone-containing gas is 50 g / m 3~250g / m 3 It is preferable that the thickness is 50 g / m 3 ~220g / m 3 It is more preferable that the ozone is added to the cellulose raw material in an amount of 0.1 to 30 parts by mass, and more preferably 5 to 30 parts by mass, based on 100 parts by mass of the solid content of the cellulose raw material. The ozone treatment temperature is preferably 0°C to 50°C, and more preferably 20°C to 50°C. The ozone treatment time is not particularly limited, but is about 1 to 360 minutes, and is preferably about 30 to 360 minutes. When the ozone treatment conditions are within these ranges, the cellulose raw material can be prevented from being excessively oxidized and decomposed, and the yield of oxidized cellulose is good. After the ozone treatment, an oxidizing agent may be used to perform a post-oxidation treatment. The oxidizing agent used in the post-oxidation treatment is not particularly limited, but examples thereof include chlorine compounds such as chlorine dioxide and sodium chlorite, oxygen, hydrogen peroxide, persulfuric acid, and peracetic acid. For example, these oxidizing agents are dissolved in a polar organic solvent such as water or alcohol to prepare an oxidizing agent solution, and the cellulose raw material is immersed in the solution to perform the post-oxidation treatment.

[0062] The amount of carboxyl groups in the carboxylated cellulose raw material can be adjusted by controlling the reaction conditions such as the amount of the oxidizing agent added and the reaction time.

[0063] <Carboxyalkylation of cellulose raw materials> As an example of a chemically modified cellulose raw material, a cellulose raw material to which a carboxyalkyl group such as a carboxymethyl group is ether-bonded (carboxyalkylated cellulose raw material) can be used. Such raw materials may be commercially available, or may be produced by carboxyalkylating the above-mentioned cellulose raw material by a known method. The degree of carboxyalkyl substitution per anhydrous glucose unit of cellulose is preferably 0.01 to 0.50. The upper limit is preferably 0.40 or less. If the degree of carboxyalkyl substitution exceeds 0.50, dissolution in water occurs easily, and the fiber form cannot be maintained in water. In order to obtain the effect of carboxyalkylation, it is necessary to have a certain degree of substitution. For example, if the degree of substitution is less than 0.02, depending on the application, the advantage of introducing a carboxyalkyl group may not be obtained. Therefore, the degree of carboxyalkyl substitution is preferably 0.02 or more, more preferably 0.05 or more, more preferably 0.10 or more, more preferably 0.15 or more, more preferably 0.20 or more, and more preferably 0.25 or more. The degree of carboxyalkyl substitution can be adjusted by controlling the amount of the carboxyalkylating agent to be reacted, the amount of the mercerizing agent, the composition ratio of water to the organic solvent, and the like.

[0064] In this specification, anhydroglucose unit means each anhydroglucose (glucose residue) constituting cellulose. In addition, the degree of carboxyalkyl substitution (also called the degree of etherification) indicates the ratio of hydroxyl groups in the glucose residues constituting cellulose that are substituted with carboxyalkyl ether groups (the number of carboxyalkyl ether groups per glucose residue). The degree of carboxyalkyl substitution is sometimes abbreviated as DS.

[0065] The method for determining the degree of carboxyalkyl substitution is as follows: Weigh out approximately 2.0 g of the sample and place it in a 300 mL Erlenmeyer flask with a stopper. Add 100 mL of nitric acid methanol (a solution of 100 mL of concentrated nitric acid added to 1000 mL of methanol) and shake for 3 hours to convert the salt-type carboxyalkylated cellulose to hydrogen-type carboxyalkylated cellulose. Weigh out 1.5 to 2.0 g of hydrogen-type carboxyalkylated cellulose (absolutely dry) and place it in a 300 mL Erlenmeyer flask with a stopper. Moisten with 15 mL of 80% methanol, add 100 mL of 0.1 N-NaOH, and shake at room temperature for 3 hours. Using phenolphthalein as an indicator, back-titrate the excess NaOH with 0.1 N-H2SO4, and calculate the degree of carboxyalkyl substitution (DS value) using the following formula. A = [(100 × F'-0.1N-H2SO4 (mL) × F) × 0.1] / (bone-dry mass of hydrogen-type carboxyalkylated cellulose (g)) Carboxyalkyl substitution degree = 0.162 x A / (1-0.058 x A) F': Factor of 0.1N-H2SO4 F: Factor of 0.1N NaOH.

[0066] The degree of carboxyalkyl substitution in the carboxyalkylated cellulose feedstock before fibrillation and the degree of carboxyalkyl substitution in the carboxyalkylated cellulose fibers after fibrillation are usually the same.

[0067] As an example of a method for producing a carboxyalkylated cellulose feedstock, the production of a carboxymethylated cellulose feedstock is described below.

[0068] First, the cellulose raw material is mixed with a solvent and a mercerizing agent, and the cellulose raw material is mercerized at a reaction temperature of 0 to 70° C., preferably 10 to 60° C., for a reaction time of 15 minutes to 8 hours, preferably 30 minutes to 7 hours. Next, a carboxymethylating agent is added in an amount of 0.05 to 10.0 times the amount of glucose residue by mole, and carboxymethylation is carried out at a reaction temperature of 30 to 90° C., preferably 40 to 80° C., for a reaction time of 30 minutes to 10 hours, preferably 1 hour to 4 hours.

[0069] As the solvent, 3 to 20 times by mass of water or an organic solvent or a mixture thereof can be used. Examples of the organic solvent include, but are not limited to, alcohols such as methanol, ethanol, N-propyl alcohol, isopropyl alcohol, N-butanol, isobutanol, and tertiary butanol, ketones such as acetone, diethyl ketone, and methyl ethyl ketone, as well as dioxane, diethyl ether, benzene, and dichloromethane. Among these, monohydric alcohols having 1 to 4 carbon atoms are preferred because of their excellent compatibility with water, and monohydric alcohols having 1 to 3 carbon atoms are more preferred. As the mercerizing agent, it is preferred to use 0.5 to 20 times by mole of an alkali metal hydroxide per anhydrous glucose residue of the cellulose raw material, specifically sodium hydroxide or potassium hydroxide. As the carboxymethylating agent, monochloroacetic acid, sodium monochloroacetate, methyl monochloroacetate, ethyl monochloroacetate, and isopropyl monochloroacetate can be mentioned. Among these, monochloroacetic acid or sodium monochloroacetate is preferred in terms of the ease of availability of the raw material. The amount of the carboxymethylating agent used is not particularly limited, but in one embodiment, it is preferably added in the range of 0.5 to 1.5 mol per anhydrous glucose unit of cellulose. The lower limit of the above range is more preferably 0.6 mol or more, even more preferably 0.7 mol or more, and the upper limit is more preferably 1.3 mol or less, even more preferably 1.1 mol or less. The carboxymethylating agent can be added to the reactor as, for example, a 5 to 80 mass % aqueous solution, more preferably 30 to 60 mass %, but is not limited thereto, or can be added in a powder state without dissolving.

[0070] The molar ratio of the mercerizing agent to the carboxymethylating agent (mercerizing agent / carboxymethylating agent) is generally 0.90 to 2.45 when monochloroacetic acid or sodium monochloroacetate is used as the carboxymethylating agent. The reason is that if it is less than 0.90, the carboxymethylation reaction may be insufficient, and unreacted monochloroacetic acid or sodium monochloroacetate may remain and be wasted, and if it exceeds 2.45, a side reaction between the excess mercerizing agent and monochloroacetic acid or sodium monochloroacetate may proceed, resulting in the production of an alkali metal glycolate, which may be uneconomical.

[0071] When carboxymethylating a cellulose raw material, there are usually two methods: a method in which both mercerization and carboxymethylation are performed in a solvent mainly composed of water (aqueous medium method), and a method in which both mercerization and carboxymethylation are performed in a mixed solvent of water and an organic solvent (solvent method). In the present invention, a solvent mainly composed of water may be used for mercerization, and a mixed solvent of an organic solvent and water may be used for carboxymethylation. By doing so, even if the crystallinity of cellulose is maintained at 50% or more, a carboxymethylated cellulose raw material in which carboxymethyl groups are introduced uniformly rather than locally (i.e., the absolute value of the anionization degree is small) can be economically obtained. Specifically, for example, but not limited to, a carboxymethylated cellulose raw material can be obtained in which the crystallinity of cellulose type I is 50% or more, the degree of carboxymethyl substitution is 0.20 to 0.50, and the degree of anionization is 0.10 meq / g to 2.00 meq / g.

[0072] A solvent that mainly uses water (a solvent that is mainly made of water) refers to a solvent that contains water at a ratio of more than 50% by mass. The amount of water in the solvent that is mainly made of water is preferably 55% by mass or more, more preferably 60% by mass or more, more preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and even more preferably 95% by mass or more. Particularly preferably, the solvent that is mainly made of water is 100% by mass (i.e., water). The higher the amount of water during mercerization, the more advantageously the carboxymethyl group is introduced more uniformly into the cellulose. As the solvent other than water in the solvent that is mainly made of water (used in a mixture with water), the organic solvent described above can be used. The amount of the organic solvent in the solvent that is mainly made of water is preferably 45% by mass or less, more preferably 40% by mass or less, more preferably 30% by mass or less, more preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and more preferably 0% by mass.

[0073] It is preferable to add an organic solvent or an aqueous solution of an organic solvent to the reactor simultaneously with the addition of the carboxymethylating agent, or before or immediately after the addition of the carboxymethylating agent, or to appropriately reduce the organic solvent other than water used in the mercerization treatment by reducing pressure or the like to form a mixed solvent of water and an organic solvent, and to proceed with the carboxymethylation reaction in this mixed solvent of water and an organic solvent. The timing of adding or reducing the organic solvent may be any time between the end of the mercerization reaction and immediately after the addition of the carboxymethylating agent, and is not particularly limited, but is preferably within 30 minutes before or after the addition of the carboxymethylating agent, for example.

[0074] The ratio of the organic solvent in the mixed solvent during carboxymethylation is preferably 20% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, even more preferably 45% by mass or more, and particularly preferably 50% by mass or more, based on the total amount of water and organic solvent. The higher the ratio of the organic solvent, the more likely it is that the substitution of carboxymethyl groups will occur uniformly, and the more stable the quality of the carboxymethylated cellulose raw material obtained will be. The upper limit of the ratio of the organic solvent is not limited, and may be, for example, 99% by mass or less. Considering the cost of the organic solvent to be added, it is preferably 90% by mass or less, more preferably 85% by mass or less, even more preferably 80% by mass or less, and even more preferably 70% by mass or less.

[0075] The reaction medium for carboxymethylation (a mixed solvent of water and an organic solvent, etc., not containing cellulose) preferably has a lower proportion of water (in other words, a higher proportion of organic solvent) than the reaction medium for mercerization. By satisfying this range, the crystallinity of the resulting carboxymethylated cellulose raw material is easily maintained, and the fiber of the present invention can be obtained more efficiently. In addition, when the reaction medium for carboxymethylation has a lower proportion of water (a higher proportion of organic solvent) than the reaction medium for mercerization, there is also an advantage that when transferring from the mercerization reaction to the carboxymethylation reaction, a mixed solvent for the carboxymethylation reaction can be formed by a simple means of adding a desired amount of organic solvent to the reaction system after the mercerization reaction is completed.

[0076] In carboxymethylation, the effective utilization rate of the carboxymethylating agent is preferably 15% or more. More preferably, it is 20% or more, further preferably, it is 25% or more, and particularly preferably, it is 30% or more. The effective utilization rate of the carboxymethylating agent refers to the ratio of the carboxymethyl groups introduced into cellulose among the carboxymethyl groups in the carboxymethylating agent. By using a solvent mainly composed of water during mercerization and a mixed solvent of water and an organic solvent during carboxymethylation, it is possible to obtain a carboxymethylated cellulose raw material with a high effective utilization rate of the carboxymethylating agent (i.e., economically without greatly increasing the amount of the carboxymethylating agent used). The upper limit of the effective utilization rate of the carboxymethylating agent is not particularly limited, but in reality, the upper limit is about 80%. The effective utilization rate of the carboxymethylating agent is sometimes abbreviated as AM.

[0077] The effective utilization rate of the carboxymethylating agent is calculated as follows: AM = (DS × moles of cellulose) / moles of carboxymethylating agent DS: Degree of carboxymethyl substitution (measurement method will be described later) Molar number of cellulose: Pulp mass (dry mass when dried at 100°C for 60 minutes) / 162 (162 is the molecular weight per glucose unit of cellulose).

[0078] <Phosphate esterification of cellulose raw materials> As an example of a chemically modified cellulose raw material, a phosphoric acid esterified cellulose raw material can be used. Examples of the esterification method include a method of mixing a powder or an aqueous solution of a compound having a phosphoric acid group with the cellulose raw material, and a method of adding an aqueous solution of a compound having a phosphoric acid group to a slurry of the cellulose raw material. Examples of compounds having a phosphoric acid group include phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium phosphite, potassium phosphite, sodium hypophosphite, potassium hypophosphite, sodium pyrophosphate, sodium metaphosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, potassium pyrophosphate, potassium metaphosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium pyrophosphate, and ammonium metaphosphate. Phosphate groups can be introduced into the cellulose raw material by using one or more of these in combination. Among these, phosphoric acid, sodium salts of phosphoric acid, potassium salts of phosphoric acid, and ammonium salts of phosphoric acid are preferred from the viewpoints of high efficiency of phosphoric acid group introduction, ease of defibration in the defibration step described below, and ease of industrial application. Sodium dihydrogen phosphate and disodium hydrogen phosphate are particularly preferred. In addition, the compound having a phosphate group is preferably used in the form of an aqueous solution, since this allows the reaction to proceed uniformly and increases the efficiency of the introduction of the phosphate group. The pH of the aqueous solution of the compound having a phosphate group is preferably 7 or less, since this increases the efficiency of the introduction of the phosphate group, but is preferably 3 to 7 in terms of suppressing hydrolysis of the fibers.

[0079] The following method can be mentioned as an example of a method for producing a phosphoric acid esterified cellulose raw material. A compound having a phosphoric acid group is added to a suspension of the cellulose raw material having a solid content concentration of 0.1 to 10% by mass while stirring to introduce a phosphoric acid group into the cellulose. When the cellulose raw material is taken as 100 parts by mass, the amount of the compound having a phosphoric acid group added is preferably 0.2 to 500 parts by mass, more preferably 1 to 400 parts by mass, in terms of the amount of phosphorus element.

[0080] From the viewpoint of suppressing hydrolysis of cellulose after dehydrating the obtained suspension of phosphorylated cellulose raw material, it is preferable to heat treat it at 100 to 170° C. Furthermore, during the heat treatment, it is preferable to heat it at 130° C. or less, preferably 110° C. or less while water is contained, and after removing the water, heat treat it at 100° C. to 170° C.

[0081] The degree of phosphate substitution per glucose unit of the phosphorylated cellulose raw material is preferably 0.001 or more and less than 0.40. The degree of phosphate substitution in the phosphorylated cellulose raw material before fibrillation is usually the same as the degree of phosphate substitution in the phosphorylated cellulose fiber after fibrillation.

[0082] <Fibrillation> The chemically modified cellulose raw material is defibrated or beaten to obtain fibrillated chemically modified cellulose fibers. The defibration or beating in the fibrillation is preferably performed in a wet manner (i.e., in the form of a dispersion in which water or the like is used as a dispersion medium) using a refiner such as a disk type, conical type, or cylinder type, a high-speed defibrator, a shear type mixer, a colloid mill, a high-pressure jet disperser, a beater, a PFI mill, a kneader, a disperser, or the like, but is not particularly limited to these devices and may be any device that imparts mechanical defibration force in a wet manner.

[0083] The solid content of the raw material in the dispersion of the chemically modified cellulose raw material to be fibrillated is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, more preferably 1.0% by mass or more, and even more preferably 2.0% by mass or more. The upper limit of the concentration is preferably 40% by mass or less, more preferably 30% by mass or less, more preferably 10% by mass or less, and even more preferably 8% by mass or less. The dispersion medium is preferably water.

[0084] The pH of the dispersion of the chemically modified cellulose raw material to be fibrillated is preferably 7.0 or less, more preferably 6.0 or less, and even more preferably 5.0 or less. There is no particular lower limit for the pH, and it is usually 2.0 or more, preferably 3.0 or more, and more preferably 3.5 or more. The pH can be adjusted by adding an acid such as hydrochloric acid to the dispersion.

[0085] Before preparing a dispersion for fibrillation, the chemically modified cellulose raw material obtained by the above method may be dried and pulverized in advance. The dry-pulverized chemically modified cellulose raw material may then be dispersed in a dispersion medium and subjected to fibrillation (wet). The apparatus used for dry pulverization of the raw material is not particularly limited, and examples thereof include impact mills such as hammer mills and pin mills, media mills such as ball mills and tower mills, and jet mills.

[0086] As described above, fibrillation is carried out in such a range that the average fiber diameter is maintained at 500 nm or more, preferably 1 μm or more, and more preferably 10 μm or more. The upper limit of the average fiber diameter is preferably 60 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and even more preferably 20 μm or less. By carrying out moderate fibrillation to such an extent that the average fiber diameter falls within this range, the cellulose fiber exhibits higher water retention than undefibrated cellulose fibers, and even in small amounts, a higher strength imparting effect and a higher yield improvement effect can be obtained compared to finely defibrated cellulose nanofibers.

[0087] As described above, it is preferable to perform fibrillation so as to improve the fibrillation rate (f0) of the chemically modified cellulose raw material before fibrillation. If the fibrillation rate of the fibrillated chemically modified cellulose fiber is f, the difference in the fibrillation rates Δf=f-f0 should be greater than 0, and is preferably 0.1% or more, more preferably 0.2% or more, more preferably 0.3% or more, more preferably 1.0% or more, and even more preferably 2.5% or more. The fibrillation rate (Fibrillation %) can be measured using a fractionator manufactured by Valmet Ltd. EXAMPLES

[0088] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited thereto. Unless otherwise specified, parts and % indicate parts by mass and % by mass.

[0089] Example 1 According to a standard method, NBKP (manufactured by Nippon Paper Industries Co., Ltd.) was oxidized using TEMPO to produce a carboxylated cellulose raw material with a carboxyl group amount of 1.42 mmol / g. An aqueous dispersion with a solid content concentration of 4 mass% was prepared from the obtained raw material, and the dispersion was treated for 10 minutes using a lab refiner manufactured by Aikawa Iron Works Co., Ltd. to prepare fibrillated carboxylated cellulose fiber. The physical properties of the obtained fiber were measured as shown in Table 1. The measurement methods for the physical properties were as described above. The results are shown in Table 1.

[0090] Example 2 A fibrillated carboxylated cellulose fiber was prepared in the same manner as in Example 1, except that a Top Finer manufactured by Aikawa Iron Works Co., Ltd. was used. The results are shown in Table 1.

[0091] Example 3 Except for changing the solid content concentration of the raw material from 4% by mass to 2% by mass, the same procedure as in Example 2 was performed to prepare fibrillated carboxylated cellulose fibers. The results are shown in Table 1.

[0092] Example 4 A fibrillated carboxylated cellulose fiber was prepared in the same manner as in Example 1, except that a carboxylated cellulose raw material having a carboxyl group amount of 0.60 mmol / g was used. The results are shown in Table 1.

[0093] Example 5 In a twin-shaft kneader adjusted to a rotation speed of 100 rpm, 130 parts of water and 20 parts of sodium hydroxide dissolved in 100 parts of water were added, and 100 parts of hardwood pulp (LBKP, manufactured by Nippon Paper Industries Co., Ltd.) was added based on the dry mass when it was dried at 100 ° C for 60 minutes. The mixture was stirred and mixed at 30 ° C for 90 minutes to prepare a mercerized cellulose raw material. Further, while stirring, 100 parts of isopropanol (IPA) and 60 parts of sodium monochloroacetate were added, and after stirring for 30 minutes, the mixture was heated to 70 ° C and carboxymethylation reaction was carried out for 90 minutes. The concentration of IPA in the reaction medium during the carboxymethylation reaction was 30%. After the reaction was completed, the mixture was neutralized with acetic acid to about pH 7, and a carboxymethylated cellulose raw material (sodium salt) with a carboxymethyl substitution degree of 0.21 and a crystallinity of cellulose type I of 72% was obtained. The effective utilization rate of the carboxymethylating agent was 29%. The methods for measuring the degree of carboxymethyl substitution and the crystallinity of cellulose type I, and the method for calculating the effective utilization rate of the carboxymethylating agent are as described above.

[0094] The obtained carboxymethylated cellulose raw material was dispersed in water at a solid content concentration of 4% by mass, and the dispersion was treated for 10 minutes using a lab refiner manufactured by Aikawa Iron Works Co., Ltd. to prepare fibrillated carboxymethylated cellulose fibers. The results are shown in Table 1.

[0095] Example 6 Fibrillated carboxymethyl cellulose fibers were prepared in the same manner as in Example 4, except that the solid content concentration of the aqueous dispersion to be fibrillated was changed from 4% by mass to 2% by mass, and Top Finer manufactured by Aikawa Iron Works Co., Ltd. was used. The results are shown in Table 1.

[0096] Example 7 A fibrillated carboxymethylated cellulose fiber was prepared in the same manner as in Example 5, except that a carboxymethylated cellulose raw material having a carboxymethyl substitution degree of 0.36 was used. The results are shown in Table 1.

[0097] Comparative Example 1 An aqueous dispersion with a solid content of 4% by mass was prepared using softwood pulp (NBKP, manufactured by Nippon Paper Industries Co., Ltd.) as the raw material, and the dispersion was treated for 10 minutes using a Top Finer manufactured by Aikawa Iron Works Co., Ltd. to prepare cellulose fibers. The results are shown in Table 1.

[0098] [Table 1]

[0099] The results in Table 1 show that the fibrillated chemically modified cellulose fibers of the present invention (Examples 1 to 7) have higher water retention capacity than Comparative Example 1 which was not chemically modified.

[0100] Example 8 5.00 g (bone-dry) of bleached unbeaten kraft pulp (NBKP, Nippon Paper Industries Co., Ltd., brightness 85%) derived from coniferous trees was added to 500 ml of an aqueous solution containing 39 mg (0.05 mmol per 1 g of bone-dry cellulose) of TEMPO (Sigma Aldrich) and 514 mg (1.0 mmol per 1 g of bone-dry cellulose) of sodium bromide, and the mixture was stirred until the pulp was uniformly dispersed. An aqueous solution of sodium hypochlorite was added to the reaction system so that the sodium hypochlorite concentration was 5.5 mmol / g, and the oxidation reaction was started at room temperature. The pH of the system decreased during the reaction, but 3 M aqueous sodium hydroxide was added successively to adjust the pH to 10. The reaction was terminated when the sodium hypochlorite was consumed and the pH of the system no longer changed. After the reaction, the mixture was adjusted to pH 2 by adding hydrochloric acid, filtered through a glass filter, and the pulp was separated. The separated pulp was thoroughly washed with water to obtain TEMPO-oxidized pulp (carboxylated cellulose raw material). The pulp yield was 90%, the time required for the oxidation reaction was 90 minutes, the amount of carboxyl groups was 1.37 mmol / g, and the pH was 4.5.

[0101] An aqueous dispersion of the obtained TEMPO oxidized pulp with a solid content concentration of 2.0% by mass was prepared, and a 5% aqueous NaOH solution and sodium bicarbonate were added to adjust the pH to 7.5, followed by treatment for 10 minutes using a Top Finer (manufactured by Aikawa Iron Works Co., Ltd.) to obtain fibrillated carboxylated cellulose fibers. The obtained fibers were measured for each of the physical properties listed in Table 2. The methods for measuring each physical property were as described above. The results are shown in Table 2.

[0102] Example 9 An aqueous dispersion with a solids concentration of 4% by mass of the TEMPO oxidized pulp obtained in Example 8 was prepared, and a 5% NaOH aqueous solution and sodium bicarbonate were added to adjust the pH to 8.6, followed by treatment for 10 minutes using a lab refiner manufactured by Aikawa Iron Works Co., Ltd. to obtain fibrillated carboxylated cellulose fibers. The results are shown in Table 2.

[0103] Example 10 An aqueous dispersion with a solids concentration of 30% by mass of the TEMPO oxidized pulp obtained in Example 8 was prepared and subjected to two-pass treatment using a lab refiner manufactured by Aikawa Iron Works Co., Ltd. to obtain fibrillated carboxylated cellulose fibers. The results are shown in Table 2.

[0104] Example 11 In a twin-shaft kneader adjusted to a rotation speed of 100 rpm, 130 parts of water and 20 parts of sodium hydroxide dissolved in 100 parts of water were added, and 100 parts of bleached unbeaten kraft pulp derived from broadleaf trees (manufactured by Nippon Paper Industries Co., Ltd., LBKP) was added in terms of dry mass when dried at 100 ° C for 60 minutes. The mixture was stirred and mixed at 30 ° C for 90 minutes to prepare a mercerized cellulose raw material. Further, while stirring, 100 parts of isopropanol (IPA) and 60 parts of sodium monochloroacetate were added, and after stirring for 30 minutes, the mixture was heated to 70 ° C and carboxymethylation reaction was carried out for 90 minutes. The concentration of IPA in the reaction medium during the carboxymethylation reaction was 30%. After the reaction was completed, the mixture was neutralized with acetic acid to about pH 7 to obtain carboxymethylated pulp (sodium salt).

[0105] The obtained carboxymethylated pulp (carboxymethylated cellulose raw material) was fibrillated in the same manner as in Example 8 to prepare fibrillated carboxymethylated cellulose fibers. The results are shown in Table 2.

[0106] Example 12 Carboxymethylated pulp produced in the same manner as in Example 11 was dry-ground and then fibrillated in the same manner as in Example 9 to obtain fibrillated carboxymethylated cellulose fibers. The results are shown in Table 2.

[0107] [Table 2]

[0108] As shown in Table 2, the fibrillated chemically modified cellulose fibers have a moderately low B-type viscosity and high thixotropy. Such fibers are expected to perform well in a wide range of applications.

Claims

1. A fibrillated chemically modified cellulose fiber having a crystallinity of 50% or more for cellulose I type, a degree of anionization of 0.10 meq / g or more and 2.00 meq / g or less, an average fiber diameter of 10 μm or more, an aspect ratio of 10 to 100, and a water retention capacity of 15 or more, The water retention capacity was measured by preparing 40 mL of a slurry having a solid content of 0.3% by mass using water, centrifuging the slurry at 25,000 G at 30° C. for 30 minutes in a centrifuge to separate the aqueous phase and the sediment, and measuring the water retention capacity according to the following formula: Water retention capacity=(B+C-0.003×A) / (0.003×A-C) (where A is the mass of the slurry subjected to centrifugation, B is the mass of the separated sediment, and C is the mass of solids in the separated aqueous phase). It is calculated using A fibrillated, chemically modified cellulose fiber used as a papermaking additive.

2. 2. The fibrillated chemically modified cellulose fiber for use as a papermaking additive according to claim 1, which has a Brookfield viscosity (25°C, 60 rpm) of 2,500 mPa·s or less when dispersed in water at 1% by mass solids.

3. 2. The fibrillated chemically modified cellulose fiber for use as a papermaking additive according to claim 1, wherein, when the fiber is dispersed in water with a solid content of 1% by mass, the value (A / B) of viscosity A measured at a shear rate of 0.01 / sec divided by viscosity B measured at a shear rate of 1000 / sec is 100 or more.

4. The fibrillated chemically modified cellulose fiber for use as a papermaking additive according to claim 3, wherein when the fiber is dispersed in water at a solid content of 1% by mass, the fiber has a viscosity A of 1,000 to 10,000,000 mPa·s measured at a shear rate of 0.01 / sec and a viscosity B of 1 to 1,000 mPa·s measured at a shear rate of 1000 / sec.

5. The fibrillated chemically modified cellulose fiber for use as a papermaking additive according to claim 3 or 4, wherein the viscosity (25°C, 60 rpm) of an aqueous dispersion having a solid content of 1% by mass is 40 to 4000 mPa·s.

6. The fibrillated, chemically modified cellulose fiber for use as a papermaking additive according to any one of claims 1 to 5, wherein the chemically modified cellulose in the fibrillated, chemically modified cellulose fiber is a carboxylated cellulose obtained by oxidizing a cellulose raw material with an N-oxyl compound, a compound selected from the group consisting of bromides, iodides and mixtures thereof, and an oxidizing agent.

7. The fibrillated, chemically modified cellulose fiber for use as a papermaking additive according to claim 6, wherein the chemically modified cellulose in the fibrillated, chemically modified cellulose fiber is a carboxylated cellulose having a carboxyl group content of 0.1 to 2.5 mmol / g relative to the bone dry mass of the fibrillated, chemically modified cellulose fiber.

8. The fibrillated, chemically modified cellulose fiber for use as a papermaking additive according to any one of claims 1 to 5, wherein the chemically modified cellulose in the fibrillated, chemically modified cellulose fiber is carboxymethyl cellulose.

9. The fibrillated, chemically modified cellulose fiber for use as a papermaking additive according to claim 8, wherein the chemically modified cellulose in the fibrillated, chemically modified cellulose fiber is a carboxymethylated cellulose having a carboxymethyl substitution degree per glucose unit of the chemically modified cellulose of 0.01 to 0.50.

Citation Information

Patent Citations

  • Modified finely fibrillated cellulose, method for producing the same, paper sheet incorporated with modified finely fibrillated cellulose, and coated paper produced by using modified finely fibrillated cellulose

    JP2002194691A

  • Viscous water base composition and method for producing the same

    JP2017110085A

  • Composite material and molded body using same

    WO2014087767A1

  • Metal-containing cellulose fiber, sanitary thin paper using same, and absorbent article

    WO2017014255A1

  • Paper containing microfibril cellulose fiber

    WO2019189611A1